The Notion of Linguacultureme and Non-Equivalent Lexicon in Different Cultures - qizi, Sharipova Sarvinoz Sayfiddin (PT. Antis International Publisher, 2024)
The article focuses on the notions which have sometimes do not have the alternatives in other languages including linguaculteremes, realia. It takes a close look to the lexicon of several languages and makes some comparisons on the stated notions.